An Integrated Simulation of Tsunami Hazard and Human Evacuation in La Punta, Peru - Mas, Erick; Adriano, Bruno; Koshimura, Shunichi (Journal of disaster research, 2013)
The 2011 Great East Japan earthquake and tsunami was a magnitude 9.0 Mw event that destroyed most structural tsunami countermeasures. However, approximately 90% of the estimated population at risk from the tsunami survived due to a rapid evacuation to higher ground or inland. Thus, tsunami evacuation is the most effective measure to reduce casualties. In this paper, we applied a new developed evacuation model integrated with the numerical simulation of tsunami for casualty estimation. This tool is to support decisions in disaster management and disaster prevention education. The model was developed in NetLogo, a multi-agent programming language and modeling environment for simulating complex phenomena. Geographic Information Systems (GIS) datasets are used as spatial input information for road and shelter locations. The TUNAMI model of Tohoku University is used for the integration of tsunami numerical simulation results. In this paper, the study is performed in a tsunami threatened urban area of Callao, Peru, called La Punta. Results show the various contributions of the model to disaster management and scenario analysis. Among the contributions are the casualty estimation in a tsunami risk area and the analysis of the spatial distribution of vertical evacuation shelters.